Cu-ZrO2 catalysts with highly dispersed Cu nanoclusters derived from ZrO2@ HKUST-1 composites for the enhanced CO2 hydrogenation to methanol - Yu, Jiahui; Liu, Shuai; Mu, Xueliang; Yang, Gang; Luo, Xiang; Lester, Edward; Wu, Tao (Elsevier, 2021)
In this study, a series of Cu-ZrO2 catalysts with highly dispersed Cu nanoclusters were prepared via the calcination and reduction of ZrO2@HKUST-1 precursors. These catalysts demonstrated an outstanding selectivity in the yield of methanol during CO2 hydrogenation. The space-time yield (STY) of methanol is 5.2 times higher than that of those similar catalysts reported by other researchers, which were prepared using conventional method and tested under the same testing conditions. Density functional theory (DFT) study revealed that the activation of CO2 occurs at the Cu-ZrO2 interfaces and facilitates the hydrogenation of CO2 to methanol. It is concluded that the controlled formation of the highly dispersed Cu nanoclusters not only provides a large number of highly efficient active centers for CO2 hydrogenation, but also leads the generation of more Cu-ZrO2 interfaces. These two effects contribute to the superior catalytic performance of the nano Cu-ZrO2 catalyst in CO2 hydrogenation.